Engaging High Water Users in Water Conservation #2: High Water Users’ Water-Related Behaviors and Willingness to Act - Pei-wen Huang; Alexa J. Lamm (EDIS)
Approximately 50% of Floridians’ daily water consumption is used for outdoor purposes, such as landscape irrigation; this is 20% higher than the national average. In order to alleviate the pressure on the precious water resources in Florida from various demands, increased public awareness and engagement in water conservation is needed especially among high water users. This 4-page fact sheet is the second in a series discussing how Extension can improve high water users’ engagement in water conservation with a focus on high water users’ water-related behavior and willingness to act. Written by Pei-wen Huang and Alexa J. Lamm, and published by the Department of Agricultural Education and Communication, July 2016.